Supply Chain Analysis Of Copra (Empirical Study in North Sumatra and Aceh) - Muhammad Buhari Sibuea; Ayu Ayu Lestari; Faiz Faiz Ahmad; Nurhadida Nasution (JASc (Journal of Agribusiness Sciences), 2021)
The research was conducted in Air Joman, Asahan Regency, because this area is one of the centers for coconut production in North Sumatra. This research is very important because of the economic prospects and the uniqueness of the supply chain which includes the two regions of North Sumatra and Aceh Provinces, where business costs are still affordable and cheap so that it can provide benefits for copra producers. The research objective was to analyze the supply of raw materials and the efficiency of copra marketing. The data obtained was in the form of primary data from copra craftsmen in Air Joman, North Sumatra and Aceh Idi. Secondary data were obtained from related institutions such as the Department of Industry and Trade, the Government of Asahan Regency and other institutions. To analyze the supply of copra raw material and marketing efficiency use by descriptive analysis methods.The results showed that there were two supply chains of raw materials, namely (1) the first supply chain started from coconut farmers in Air Joman then distributed to copra producers / consumers and (2) the second supply chain started from coconut farmers in Aceh Idi then to agents in Aceh Idi then distributed to collectors in Aceh Idi and finally distributed to copra craftsmen / consumers in Air Joman. It can be seen that the flow of raw materials that occurs includes two provinces, namely Asahan, North Sumatra and Aceh Idi Aceh. Even so, it turns out that the cost is cheap and affordable so that it becomes something phenomenal. While the marketing channel has one channel, namely from copra entrepreneurs to be sold directly to the final consumer with an efficiency value of 2.07% which means very efficient.The study recommends that the craftsmen make efforts to process copra into oil and flour so that they do not need to sell them to oil refineries to improve their income. And to make business more efficient by increasing production with better and modern technology.